MicroRNA‐135a‐5p reduces P2X7‐dependent rise in intracellular calcium and protects against excitotoxicity. Issue 1 (9th May 2019) - Reigada, David; Calderón‐García, Andrés Ángel; Soto‐Catalán, Manuel; Nieto‐Díaz, Manuel; Muñoz‐Galdeano, Teresa; del Águila, Ángela; Maza, Rodrigo M.
Abstract: Excitotoxic cell death because of the massive release of glutamate and ATP contributes to the secondary extension of cellular and tissue loss following traumatic spinal cord injury (SCI). Evidence from blockage experiments suggests that over‐expression and activation of purinergic receptors, especially P2X7, produces excitotoxicity in neurodegenerative diseases and trauma of the central nervous system. We hypothesize that the down‐regulation of specific miRNAs after the SCI contributes to the over‐expression of P2X7 and that restorative strategies can be used to reduce the excitotoxic response. In the present study, we have employed bioinformatic analyses to identify microRNAs whose down‐regulation following SCI can be responsible for P2X7 over‐expression and excitotoxic activity. Additional luciferase assays validated microRNA‐135a‐5p (miR‐135a) as a posttranscriptional modulator of P2X7 . Moreover, gene expression analysis in spinal cord samples from a rat SCI model confirmed that the decrease in miR‐135a expression correlated with P2X7 over‐expression after injury. Transfection of cultures of Neuro‐2a neuronal cell line with a miR‐135a inhibitory sequences (antagomiR‐135a), simulating the reduction of miR‐135a observed after SCI, resulted in the increase of P2X7 expression and the subsequent ATP‐dependent rise in intracellular calcium concentration. Conversely, a restorative strategy employing miR‐135a mimicked reduced P2X7 expression, attenuating the increase in intracellular calcium concentration that depends on this receptor and protecting cells from excitotoxic death. Therefore, we conclude that miR‐135a is a potential therapeutic target for SCI and that restoration of its expression may reduce the deleterious effects of ATP‐dependent excitotoxicity induced after a traumatic spinal cord injury. Abstract : Excitotoxic death triggered by the release of ATP and the overexpression of P2X7 purinergic receptor contributes to extend tissue damage after CNS injuries. This study shows that miR‐135a‐5p, a microRNA downregulated after spinal cord injury, targets P2X7 to inhibit its translation, attenuating ATP‐induced excitotoxicity and protecting neural cells. Thus, therapeutic replacement of miR‐135a‐5p expression after injury may reduce damage in CNS injuries.